1. SPEAK OUT, SPEAK LOUD `KEKUATAN PERSUASIF IKLAN BICARA TENTANG KEKERASAN' - Pitakola, Dyah (FORUM, 2008)
Every ads alms to make the target audience construc it in the way intended. However, while every communication invites a certain interpretation, this invitation can be refused. Undeniably that advertising has an outstanding natural capability to raise awareness within short time and has been prooved as a unique tool in communicating social issues effectively to the target audience, However, lack of understanding about how advertising should work for the sake of audience rise a very difficult and chaos situation. Consumer insight and how we engaged it with the advertising message using the means-end chain theory approach, brought a different way of thinking about how advertising, especially public service advertising could do their job effectively in changing public behaviour and attitude. By understanding each component within the MECCAS model, advertising could force its persuasive effect to gain its objective ‘to change people’s behaviour’.